2014
DOI: 10.4149/bll_2014_150
|View full text |Cite
|
Sign up to set email alerts
|

Combined surgical treatment of lung cancer and heart diseases

Abstract: Objective: The co-incidence of lung cancer and heart disease is increasing. This can be caused by population ageing, which has more co-morbidities and most likely due to the common etiological causes of both entities, i.e. smoking, hypertension and obesity. The aim of this study was to analyze the outcomes of simultaneously performed heart surgery and pulmonary resection in a selected group of patients. Methods: From January 2002 to December 2011 we performed in our department 1115 pulmonary resections for lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The findings of this study are supported by previous studies that have shown that the one-stage approach did not increase the surgical trauma and affect postoperative recovery [ 26 ]. The cumulative survival rate in this study was 47.9% at five years.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study are supported by previous studies that have shown that the one-stage approach did not increase the surgical trauma and affect postoperative recovery [ 26 ]. The cumulative survival rate in this study was 47.9% at five years.…”
Section: Discussionsupporting
confidence: 89%
“…All the complications were treated and all the patients were discharged from the hospital except the one died of pneumonia at 1 month after surgery. The simultaneous surgeries did not increase the surgical trauma and affect postoperative recovery [26]. The cumulative 5-year survival rate is 52.9% in our series.…”
Section: Discussionmentioning
confidence: 62%
“…Simultaneous surgery has already been carried out in the 1980s for combined treatment of pulmonary neoplasia and cardiac surgical disorders. In one stage operation, CABG is performed first, considering cardiac surgery is an aseptic surgery, and cardiac revascularization is carried out first to avoid perioperative myocardial ischemia [25, 26]. Compared to a two-stage operation, a one-stage operation also has advantages including a single induction of general anesthesia, shorter overall hospital stay, and reduced cost of treatment [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 29 eligible studies were nally included in the present metaanalysis (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These studies were carried out in the following geographical regions: ve in USA (8,19,20,32,35), four in China (3,11,25,26), four in Netherlands (7,13,30,33), three in Italy (14,18,29), two in Czech Republic (12,24), two in Japan (10,16), two in Turkey (9, 15), one in Australia (34), one in Belgium (6), one in C...…”
Section: Study Searches and Characteristicsmentioning
confidence: 99%